Identidad indígena en Chile en contexto de migración, urbanización y globalización - Andrea Aravena Reyes (Les Cahiers ALHIM)
The study of indigenous migration poses great challenges, because it deals with a population that historically has been subsumed into other types of migration, and a reality that for decades had not been studied as such in Latin America. The present article addresses indigenous migration and urbanization in Chile during recent decades; it focuses upon identity and self-ascription of indigenous peoples in the context of a globalized world. In order to do this, first, it examines recent population censuses that include self-ascription to indigenous populations, and second, it analyzes information about indigenous populations in urban and migrant associations, on the bases of census data and original research.